Indicators of soil degradation in urban forests: Physical and chemical parameters - Longo, R. M.; Reis, M. S.; Yamaguchi, C. S.; Demamboro, A. C.; Bettine, S. C.; Ribeiro, Admilson Írio [UNESP]; Medeiros, Gerson Araujo de [UNESP] (WITPRESS LTD., 2012)
The fragmentation of forest habitats in urban areas has aroused increasing interest in recent years according to the growing environmental problems. The fragmentation of theses ecosystems is caused, in general, by the pressure of housing, agriculture and industry, causing losses in biodiversity and problems of soil degradation in the border areas of theses remnants. The establishment of indicators of soil degradation becomes essential for the implementation of conservation and reclamation. This study analyzes physical and chemical characteristics of soil under different forms of vegetation in the forest surrounding the Quilombo Forest, located in Campinas/SP - Brazil, and examines the possibility of using these indices as indicators of environmental degradation in urban remnants. The parameters analyzed were: specific weight natural (γn), specific weight of solids (γs) Ca, P, K, Mg, pH, organic matter, H + Al, Sum of Base (SB) Percent Base Saturation (V%), Cation Exchange Capacity (CEC). The study shows that in general the different forms of land used in the study area significantly changed (or according to) the physical aspects of soil The porosity and voids of the soil stood out as the best indicators of soil physical degradation in the layer 0-20 cm deep. In relation to chemical indices, the soil under the cultivation of cane sugar had a significantly higher pH, K, Ca, Mg and sum of bases. The areas of forest showed higher levels of phosphorus, organic matter and CEC, indicating the importance of maintaining vegetation and replacement for the cycling of organic matter.
Keywords: Remnant forest; Soil degradation; Soil physics; cation exchange capacity; forest soil; organic matter; phosphorus; soil chemistry; soil degradation; urban forestry; Brazil; Campinas; Sao Paulo [Brazil]